Fostering nursing innovation to prevent and control antimicrobial resistance using approaches from the arts and humanities - Macduff,C; Rafferty,AM; Prendiville,A; Currie,K; Castro,Sanchez E; King,C; Carvalho,F; Iedema,R (Journal of Research in Nursing, 2020)
BackgroundEfforts to address the complex global problem of antimicrobial resistance (AMR) highlight the need for imagination and innovation. However, nursing has not yet leveraged its potential to innovate to prevent AMR advancing. AimThis paper focuses on the initial phase of an ongoing research and development study that seeks to foster nursing imagination and innovation by enhancing the meaningfulness of AMR for practicing nurses and by facilitating their creative ideas.MethodsThis aim is addressed through application of arts and humanities approaches, in particular the use of visualisation, co-design and historical methods, underpinned by the Design Council Double Diamond process model. The first phase with twenty UK participants explored how hospital and community based nurses understand and respond to the priorities and consequences of antimicrobial resistance (AMR) within their everyday working lives.FindingsNurses varied in their conceptualisations of AMR and in their depictions and explanations of its meaning and priority within everyday practices. Some saw IPC and AMR as bound up together whereas others differentiated in the context of specific work activities. Insights into related reasoning and practice tactics were also generated.ConclusionThe initial project phase provides a basis for fostering nursing innovation in this important field.